PROFESSIONAL ENVY AMONG DOCTORS - Dana Mihaela Turliuc; Șerban Turliuc; Andrei Ionuț Cucu; Claudia Florida Costea (Romanian Society of Oral Rehabilitation, 2016)
Envy and jealousy are emotions or feelings that are found in all cultures of the world in all historical periods. Envy is a negative emotion which occurs when a person lacks another's possession, or the egotistical ill-feeling caused by another's achievement or superior quality or welfare. Envy is found in all professions, yet more frequently among doctors, especially among surgeons. It may be classified in surgical envy, hierarchical envy and patient-related envy. Professional envy in doctors makes socializing and interrelating difficult, as the peers are always seen as competitors and socializing with them is competition and not a collective effort directed to help the patient and to do good. The remedy for professional envy is self-discipline and devotion to the profession and to the patient, the pursuance of a higher life ideal, the aw